Civil Society and Democratization - PHATHARATHANANUNTH, Somchai (Nias Press, 2007)
This book investigates the struggle of an important social movement in Thailand, the Small Scale Farmers’ Assembly of Isan (SSFAI), and examines the role of civil society in the process of democratization. This first major work on the SSFAI demonstrates how civil society organizations in the form of social movements contribute to the democratization process in the key areas of citizenship rights. Moreover, the book also addresses two important themes in social movement’s research: the impacts of strategies and tactics on the outcomes of social movements, and the effect of organizational structure on movements’ goals and activities.